PERKEMBANGAN SMA NEGERI 1 LUBUK SIKAPING: STUDI PERUBAHAN STATUS (1955-2016) - Yoanda, Pandu Tri (RC-INSTITUT, 2019)
This paper is a study of the story of the institution, which illustrates the deveopment of educational institutions namely SMA Negeri 1 Lubuk Sikaping was bron from 1955 and going until now. This paper illustrates how the development of SMA Negeri 1 Lubuk Sikaping since it is inception until 2016 which focuses on the changing school status.the developments school starts from fillial to change in independent schools, superior classes and referral schools. So that it can see the contribution of this education to the development of education in Pasaman Regency. This writing uses a descriptive method which is supported by historical methods. The steps in this study are inseperable from historical methods and qualitative methods are often used, namely; Heusristics in the from of data colletion or information from documents and interviews with resource persons in the from of school development and managenent. Then criticism (extren and intern) then the interpretation and final writing.